Deciphering Historical Water-Quality Changes Recorded in Sediments Using eDNA - Sun, Jing; Chen, Xueping; Yu, Juan; Chen, Zheng; Liu, Lihua; Yue, Yihong; Fu, Zhiwei; Yang, Ming; Wang, Fushun (Frontiers in Environmental Science, 2021)
Reservoir sediments harbour abundant bacterial communities that are sensitive to substances transferred from the water column and might record historic water quality in environmental DNA (eDNA). The unique bacterial community along the sediment profile were retrieved based on eDNA in a reservoir to investigate potential links between water quality and the microbial population on a long-time scale. Bacterial communities in sediment samples gathered into three clusters along the depth (depths of 18-38 cm, 8-18 cm, and 1-7 cm). These three sections accumulated during three periods in which water quality was recorded in history (the pristine stage, degraded stage and remediated stage). Sediment samples from the degraded stage had lower microbial community evenness and diversity and higher microgAMBI indices than the other two sections, suggesting that poor water quality during that period was recorded in sedimental eDNA. After decades of biogeochemical cycles, statistical analysis revealed that the main factors affecting the microbial community were bromine, chlorine and high molecular-weight PAHs in sediments from the degraded stage. The relevant functional groups Dehalococcoidia, Gemmatimonadales, Sva0485, Burkholderiales and Xanthomonadales might be indicators of the historical loading of these pollutants. Amending the microgAMBI index with our functional group of pollution can better illustrate the significant long-term environmental changes caused by historic anthropogenic activities. In sediments from the pristine stage with less pollution input, DIC (dissolved inorganic carbon) from the karst landform was the dominant factor controlling microbial communities. Whereas, the surface sediments, which accumulated during the remediated stage, had more correlation with chemistry, such as sulfate and heavy metals, in the overlying water. Our research revealed that historical changes in the water condition, that can be affected by anthropogenic activities, can be depicted by changes in the bacterial communities stored in the sediment using sedimental eDNA. Assessments of the bacterial communities in the sediments, either by describing their biodiversity or using particular species as indicators, would be potential proxies to describe historical environmental development of microbial communities.